Effects of Extreme Weight Loss on Cardiometabolic Health in Children With Metabolic Syndrome: A Metabolomic Study - Liu, Jingxin; Zhu, Lin; Liao, Jing; Liu, Xiaoguang (Frontiers in Physiology, 2021)
Objectives: To evaluate the effect of extreme weight-loss programs on circulating metabolites and their relationship with cardiometabolic health in children with metabolic syndrome. Methods: This study was a quasi-experimental design with a pre-test and post-test. Thirty children with metabolic syndrome and aged 10–17 years old were recruited to an extreme weight-loss program (i.e., exercise combined with diet control). The primary outcomes included plasma metabolites, body composition, and cardiometabolic risk factors. A total of 324 metabolites were quantitatively detected by an ultra-performance liquid chromatography coupled to tandem mass spectrometry system, and the variable importance in the projection (VIP) value of each metabolite was calculated by the orthogonal projection to latent structures discriminant analysis. The fold change (FC) and p-value of each metabolite were used to screen differential metabolites with the following values: VIP > 1, p-value < 0.05, and |log2FC| > 0.25. Pathway enrichment and correlation analyses between metabolites and cardiometabolic risk factors were also performed. Result: A large effect size was observed, presenting a weight loss of -8.9 kg (Cohen’s d = 1.00, p <0.001), body mass index reduction of -3.3 kg/m2 (Cohen’s d = 1.47, p < 0.001), and body fat percent reduction of -4.1 (%) (Cohen’s d = 1.22, p <0.001) after the intervention. Similar improvements were found in total cholesterol (Cohen’s d = 2.65, p <0.001), triglycerides (Cohen’s d = 2.59, p <0.001), low-density lipoprotein cholesterol (Cohen’s d = 2.81, p <0.001), glucose metabolism, and blood pressure. A total of 59 metabolites were changed after the intervention (e.g., aminoacyl-tRNA biosynthesis, glycine, serine, and threonine metabolism; nitrogen metabolism, tricarboxylic acid cycle, and phenylalanine, tyrosine, and tryptophan biosynthesis). The changes in metabolites (e.g., amino acids, fatty acids, organic acids, and carnitine) were related to lipid metabolism improvement (p<0.05). Organic acids and carnitines were associated with changes in the body composition (p<0.05). Conclusion: Exercise combined with dietary control improved the body composition and cardiometabolic health in children with metabolic syndrome, and these changes may be related to plasma metabolites.